2020
DOI: 10.1159/000510335
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Cross-Reactive Anaphylaxis as a Different Clinical Subtype of Nonsteroidal Anti-Inflammatory Drug (NSAID) Hypersensitivity

Abstract: <b><i>Introduction:</i></b> The European Network of Drug Allergy and the European Academy of Allergy and Clinical Immunology have classified hypersensitivity reactions induced by nonsteroidal anti-inflammatory drugs (NSAIDs) into 5 phenotypes according to the pathophysiology, clinical manifestations, number of drugs involved, and the presence of underlying diseases. This classification does not include anaphylaxis as part of NSAID cross-reactivity. The objective of this study was to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This problem has also been noted in previous studies. [7][8][9][10][11][12][13] Vally et al reported an interesting group of non-asthmatic patients with respiratory symptoms induced by aspirin, similar to one patient in our study who could not be categorized using the ENDA classification. 41 We think that our classification is important, because a patient with asthma and an u/ae-type reaction to NSAIDs would not benefit from aspirin desensitization, or their asthma would be better controlled compared to those who experience an asthmatic-type reaction.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This problem has also been noted in previous studies. [7][8][9][10][11][12][13] Vally et al reported an interesting group of non-asthmatic patients with respiratory symptoms induced by aspirin, similar to one patient in our study who could not be categorized using the ENDA classification. 41 We think that our classification is important, because a patient with asthma and an u/ae-type reaction to NSAIDs would not benefit from aspirin desensitization, or their asthma would be better controlled compared to those who experience an asthmatic-type reaction.…”
Section: Discussionsupporting
confidence: 80%
“…[7][8][9][10][11] Blanca Lopez et al reported in a review that there are two additional groups that include selective NSAID-induced organ specific reactions (hepatitis, bile duct syndrome, and meningitis), and selective NSAID-induced skin/systemic manifestations (vasculitis). 12 Patients with NSAID cross-reactive anaphylaxis were described by Vasquez et al 13 In a review, three different phenotypes beyond the ENDA classification were mentioned: blended reactions (cases of cross reactors affecting both the skin and the airways, as well as other organs) 3,7,14 ; food-dependent NSAID-induced anaphylaxis [15][16][17][18] and NSAIDs-multiple selective immediate reactions (some cases may have immediate reactions to many NSAIDs but tolerate ASA). 19,20 Rising data shows that NERD is heterogeneous in terms of the order of developing symptoms, pathogenetic mechanisms involved, and type of NSAID hypersensitivity (NH) reaction (e.g., respiratory, cutaneous, and gastrointestinal symptoms).…”
Section: Introductionmentioning
confidence: 99%